O texto nos acórdãos dos tribunais - Lellis, Lélio Maximino (2008)
The knowledge of attributes of deciding texts of the judicial collective sentence genre (Acórdão genre) and, on this account, with characteristics of the Judiciary, especially those related to enunciative subjectivity, assume the choice of the corpus to be investigated, the configuration of the textual generic system in which the object of study is inserted and the elaboration of the linguistic analysis model to be employed. The corpus, analyzed through the deductive hypothetic method, is composed of six informing texts of definitive collective decision emanated from the Supreme Court of Justice, the High Court of Judicature and from the Court of Appeal of São Paulo. The choice for the Acórdão genre was due to the multiculturalism expressed in them. The system of juridical textual genres is composed of investigative, petitional, opinative and deciding subsystems, to which the Acórdão belongs to. They are originated in the juridical discursive community and correspond to the four linguistics moments of concretization of Law There are three dimensions to the analysis model applicable to Acórdão texts, which can be viewed in a triangle form: 1st the indicative of the linguistic levels (syntactic, semantic, pragmatic); 2nd the outward expression of the local and global ambit of meaningful extent (the posed and the understood); 3rd the one that points at the research prisms (form, content, ideological substrate). Through the application of the interpretative model mentioned above the results show that the Acórdão genre has a peculiar superstructure in which narration and argumentation prevail, in a general sense, even though the dominant functional type is the injunctive. The results also show that in each Acórdão text the macrostructure points at a pronounced decision about the declaration or constitution of pleaded rights by both parties. Moreover, the texts analyzed seem to have an illocutionary force characterized by maximum imperativity which does not admit disobedience by the co-enunciator. Nevertheless, they seem to express devaluation of the enunciator s face, besides refraining from partially achieving the effects of meaning related to enunciative subjectivity and intended by the enunciator, as well as resulting from the ideological substrate derived from ideologies related to judiciary institution in which the enunciator aims to represent. So, even though they are effective to the textuality principles, the acórdão texts, in their current composition, may put at risk the way in which the judiciary wishes to be known in the popular imaginary, such as, in the ideological conditions of fair arbitrator, axiologicaly impartial and neutral in relation to litigants in judiciary process, which may contribute to unstable the reality present in Brazil